2014
DOI: 10.1667/rr13359.1
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Attentional Deficits and Dopaminergic Protein Levels following Exposure to Proton Radiation

Abstract: To assess the possible neurobehavioral performance risks to astronauts from living in a space radiation environment during long-duration exploration missions, the effects of head-only proton irradiation (150 MeV/n) at low levels (25-50 cGy, approximating an astronaut's exposure during a 2-year planetary mission) were examined in adult male Long-Evans rats performing an analog of the human psychomotor vigilance test (PVT). The rodent version of PVT or rPVT tracks performance variables analogous to the human PVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 65 publications
4
45
0
Order By: Relevance
“…As long term effects of exposure to space radiation persist and can lead to carcinogenesis and central nervous system effects, as has been previously demonstrated in mouse models (4, 5, 16, 17, 2325), it is imperative to understand the early effects of radiation exposure and the metabolic changes that can contribute to genetic alterations through persistent inflammatory or oxidative responses. Urinary metabolomics can rapidly provide a snapshot of the metabolic state of an individual and as shown this first study of exposure to protons identify a significant number of metabolites that are involved in important biochemical processes.…”
Section: Discussionmentioning
confidence: 99%
“…As long term effects of exposure to space radiation persist and can lead to carcinogenesis and central nervous system effects, as has been previously demonstrated in mouse models (4, 5, 16, 17, 2325), it is imperative to understand the early effects of radiation exposure and the metabolic changes that can contribute to genetic alterations through persistent inflammatory or oxidative responses. Urinary metabolomics can rapidly provide a snapshot of the metabolic state of an individual and as shown this first study of exposure to protons identify a significant number of metabolites that are involved in important biochemical processes.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly employed tests include the Morris water maze and Barnes maze , novel object recognition, object in place recognition, (Casadesus et al 2004;Kumar et al 2013;Shukitt-Hale et al 2000;Tseng et al 2013), and contextual fear conditioning for hippocampus-dependent memory (especially spatial memory) but with strong associations with the cortex as well. Cognitive behaviors more closely associated with the frontal cortex include operant conditioning Rice et al 2009), attentional set shifting Lonart et al 2012), and psychomotor vigilance tests (Heinz et al 2008;Davis et al 2014). Anxiety and fear are commonly assessed with open field tests and elevated plus or zero mazes (Kumar et al 2013).…”
Section: Behavioral Effects a Overall Observationsmentioning
confidence: 99%
“…Reproduced from Figure 5 of . Davis et al (2014) exposed young Long-Evans rats to 25 -200 cGy head-only 150 MeV protons and tested them from 25 to 251 days post-irradiation using the rodent Psychomotor Vigilance Test (rPVT), which was adapted from a human test battery. The rPVT test uses light cues, nose-poke responses, and food rewards to measure reaction times, performance accuracy, persistence of attention, and impulsivity (premature responding) to randomized cues.…”
Section: G Tests Of Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such publications include studies suggesting that the induction of Alzheimer’s disease may be a space radiation risk (42) and attention deficits may arise following exposure to low doses of space radiation (43). Many other publications have also indicated that there are major CNS space radiation risks [e.g., (4452)].…”
Section: Introductionmentioning
confidence: 99%